2009
DOI: 10.1080/10428190903003244
|View full text |Cite
|
Sign up to set email alerts
|

Lack of prognostic value of MMP-9 expression and immunohistochemically defined germinal center phenotype in patients with diffuse large B-cell lymphoma treated with modern chemotherapy with or without CD20 antibody

Abstract: Diffuse large B-cell lymphomas (DLBCLs) are a heterogeneous group of lymphomas, with no accepted biological prognostic markers in routine clinical practice. Previously, matrix metalloproteinase (MMP-9), tissue inhibitors of matrix metalloproteinase (TIMP)- 1 and non-germinal center (GC) phenotype have been shown to associate with poor prognosis in DLBCL patients. The aim of this study was to find out whether tissue expression of gelatinases (MMP-2 and MMP-9) or their tissue inhibitors (TIMP-1 and TIMP-2) or im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…It has been proved that, compared with patients who did not receive 5-Fu based chemotherapy, patients treated with 5-Fu would lose the prognostic value of MMP-9. 46 Therefore, only patients who had not received neoadjuvant chemotherapy were recruited in our present study in order to diminish the influence of the neoadjuvant on MMPs and survival of patients.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proved that, compared with patients who did not receive 5-Fu based chemotherapy, patients treated with 5-Fu would lose the prognostic value of MMP-9. 46 Therefore, only patients who had not received neoadjuvant chemotherapy were recruited in our present study in order to diminish the influence of the neoadjuvant on MMPs and survival of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Considering Myc and its downstream regulated gene NDRG2 were also regulated by NF-kB pathway, the recruited patients who had received neoadjuvant chemotherapy would thus come up with false results. It has been proved that compared with patients who did not receive 5-FU-based chemotherapy, in patients treated with 5-FU, matrix metalloproteinase-9 would lose its prognostic value (48). So patients who had received neoadjuvant chemotherapy were excluded.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proved that compared to patients who did not receive 5-Fu based chemotherapy, when patients treated with 5-Fu, MMP-9 would lost its prognostic value. 43 Therefore, in our study, the expression of MMP-9 was examined in patients who had not received neoadjuvant chemotherapy. Moreover, study on sensitivity analysis showed that recurrence or survival of patients after surgery was differentially extended by whether the patient received initial adjuvant therapy or not, the association between prognostic value of biomarkers on disease-free and overall survival at all time points could be substantially diminished.…”
Section: Discussionmentioning
confidence: 99%